Investor Sentiment and Crash Risk in Safe Havens - Nasr, Adnen Ben; Bonato, Matteo; Demirer, Riza; Gupta, Rangan (Journal of Economics and Behavioral Studies, 2019)
This study examines the relationship between investor sentiment and intraday return dynamics for safe haven assets, with a particular focus on crash risk in these assets. Examining intraday returns for a wide range of safe havens proposed in the literature, we find that shocks to investor sentiment have a significant effect on safest havens, while the sentiment is heterogeneous both in terms of its size and direction. While the strongest effects of sentiment shocks are observed in the case of Gold, Swiss Francs and Japanese Yen, interestingly, we find that oil stands out from the rest of the pack, responding negatively to sentiment shocks, suggesting that positive shocks to sentiment (i.e. high fear) increase crash risk for this asset. Our findings also point to intra-safe haven spillover effects, with oil exhibiting a markedly different pattern. Investment and hedging implications are discussed next.